ANALISIS KEGIATAN EKSTRAKURIKULER ENGLISH DAY TERHADAP PEMBENTUKAN KARAKTER SISWA DI SD NEGERI 4 LINTONG NIHUTA KABUPATEN SAMOSIR - Sylvia Ramadhani; Hapni Laila Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the impact of the English Day extracurricular activity on character building among elementary school students. The research was conducted using a qualitative descriptive approach at SD Negeri 4 Lintong Nihuta. Data were collected through observation, interviews, and documentation related to the implementation of English Dayactivities. The findings reveal that English Day positively contributes to students’ character development, particularly in fostering confidence, responsibility, discipline, and teamwork. Students become more courageous in communicating using English, more responsible in completing assigned tasks, and more disciplined in adhering to school rules during activities. Group-based tasks such as educational games and drama performances also enhance cooperation and respect among peers. Nevertheless, challenges remain, including teachers’ limited English proficiency and a lack of activity variation and learning facilities. Overall, English Day serves not only as a medium for improving English language skills but also as an effective character education program that shapes students into more confident, disciplined, and collaborative individuals. Future implementations should emphasize teacher involvement, creative program design, and parental support to optimize outcomes.